Trubarjevo osvobajanje subjekta - Paternu, Boris (Slavistična revija, 2008)
Trubar's reorientation in the framework of the Reformation from Catholic universalism to Protestant individualism foregorunds the problem of the individual human being of the new era. However, it was eventually met with dogmatic and institutional obstruction not only on the Catholic side, but also on the Lutheran.
Keywords: Protestantism; protestantizem; Slovene literature; slovenska književnost; slovenska reformacija; Trubar, Primož, 1508-1586